ANALISIS SWOT UNTUK MANAJEMEN KEGIATAN KEMAHASISWAAN - -, Priyono - (Joglo, 2004)
ABSTRACT In many instances, using the design approach would be unwarranted and perhaps even inappropriate. This would be particularly true in situations where a firm needs to develop its strategies through a learning process. The SWOT analysis, for example, could become a process dominated by a few individuals in a closed room, similar to a classroom case study discussion. Key Words : The analysis SWOT, strategy, learning process